Desain Pengering Elektrik Untuk Pengolahan Dendeng Ikan Cakalang (Katsuwonus Pelamis) - M. Muzni Harbelubun; Tri Suyono; Iwan Gunawan; Amat Umron (Jurnal Inovasi Teknologi Terapan, 2026)
Traditional drying of skipjack jerky is still widely used by MSMEs, but it is highly weather-dependent, prone to contamination, and produces less uniform quality. This research aims to design and test a prototype of an incandescent electric dryer that is simple to operate, provides controlled drying conditions, and is easy to use. The system developed is an insulated cabinet with stainless-steel mesh racks, incandescent light heaters, forced-air circulation, and temperature and humidity sensors, monitored during a 360-minute performance test with sample mass changes. The results showed that the drying chamber temperature remained stable at 43.9–49.3 °C, the relative humidity dropped from about 47% to ±30%, and the jerky mass decreased from ±917 g to ±353 g, with a final moisture content of about 30%. Compared to sun drying, electric dryers provide faster drying rates and more stable drying patterns, making the time to achieve the target moisture content and quality between batches more predictable. These findings show that the prototype is worthy of consideration as an alternative drying technology for seafood processing MSMEs and serves as a basis for further development to improve energy efficiency and product uniformity.